2019
DOI: 10.1038/s41598-018-37204-3
|View full text |Cite
|
Sign up to set email alerts
|

A cryogenic spin-torque memory element with precessional magnetization dynamics

Abstract: We present a study of precessional magnetization switching in orthogonal spin-torque spin-valve devices at low temperatures. The samples consist of a spin-polarizing layer that is magnetized out-of-the film plane and an in-plane magnetized free and reference magnetic layer separated by non-magnetic metallic layers. We find coherent oscillations in the switching probability, characterized by high speed switching (~200 ps), error rates as low as 10−5 and decoherence effects at longer timescales (~1 ns). Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Remarkably, it has been recently demonstrated that SHE-MTJs devices can be switched with sub-ns pulses and can exhibit write error rates (WERs) below 10 #$ for pulses as short as 2 ns without fear of dielectric tunnel barrier breakdown [13]. This IPM approach offers considerable simplicity over other spintorque device alternatives: precessional switching in multi-polarizer devices requires very precise timing inherent to precessional reversal dynamics [14,15], while fast SHE switching of a perpendicular magnetized (PM) free layer requires some manner of in-plane effective-field bias (from exchange pinning, external fields, or other mechanisms) to break the axial symmetry of the FL, as well as precise pulse timing in the short pulse regime to obtain deterministic reversal [6].…”
mentioning
confidence: 99%
“…Remarkably, it has been recently demonstrated that SHE-MTJs devices can be switched with sub-ns pulses and can exhibit write error rates (WERs) below 10 #$ for pulses as short as 2 ns without fear of dielectric tunnel barrier breakdown [13]. This IPM approach offers considerable simplicity over other spintorque device alternatives: precessional switching in multi-polarizer devices requires very precise timing inherent to precessional reversal dynamics [14,15], while fast SHE switching of a perpendicular magnetized (PM) free layer requires some manner of in-plane effective-field bias (from exchange pinning, external fields, or other mechanisms) to break the axial symmetry of the FL, as well as precise pulse timing in the short pulse regime to obtain deterministic reversal [6].…”
mentioning
confidence: 99%
“…While these devices were optimized for low temperature operation and integration with superconducting circuitry, a twoterminal pMTJ device has advantages in terms of the integration density and simplicity of fabrication. Different two-terminal STT all-metallic magnetic memory elements [6,7] have also been investigated at low temperature. They have a lower impedance, but they do not simultaneously offer high switching probabilities and large readout signals, i.e.…”
mentioning
confidence: 99%
“…Easy-plane dynamics requires a ferromagnetic material with an easy-plane perpendicular to the polarization of the spin current. Previous studies have used spin valves with perpendicular spin current polarizer, which has the benefit of easy-plane in the magnetic film plane that is easy to obtain, but at the price of a complicated magnetic film stack fabrication [18][19][20]. Here we make the choice to use the spin Hall effect to inject a spin current.…”
Section: Micromagnetic Simulationsmentioning
confidence: 99%